2x + 5y = 19
x - 2y = - 4
Answer:
Step-by-step explanation:
。☆✼★ ━━━━━━━━━━━━━━ ☾
2x + 5y = 19
x - 2y = -4
Multiply the second equation by 2
2x - 4y = -8
Now we have:
2x + 5y = 19
2x - 4y = -8
Subtract the second eq from the first to get:
9y = 27
/ 9
y = 3
Now substitute this value into one of the first equations
x - 2(3) = -4
x - 6 = -4
x = 2
Thus, your answer would be option B
Have A Nice Day ❤
Stay Brainly! ヅ
- Ally ✧
。☆✼★ ━━━━━━━━━━━━━━ ☾
The sum is
Step-by-step explanation:
First term(a) = 1
Common difference(d)=2-1=1
No.of term(n)=50
Sn=n÷2(n+1)=50÷2(50+1)=1275